Analisis Kinerja Layanan dan Kepuasan Pelanggan terhadap Loyalitas Nasabah Tabungan - Annisa Aqsha Wardhana; Syarifah Hudayah; Sri Wahyuni (Faculty of Economics and Business Mulawarman University, 2017)
Research aims to know the influence of the Service Performance and Costumer Satisfaction loyality to the obligor Bank Mandiri branch Samarinda as well as to self relianthknowing variable does influential dominant among variable Service Performance and Customer Satisfaction of the Loyalty of the depositor Bank Mandiri branch self contained Samarinda.Sample on the basis Formula Solvin by Umar (2003: 146) obtained 95 or use calculationang depositor Bank Mandiri branch Samarinda.Method of data gathering used directly to the pil is interview involved with the matters discussed and give a list of question to depositor savings Bank Mandiri branch Samarinda.Analyzed data using equipment analysis multiple regression the testing done with t test, and test coefficient of determination to assistance software SPSS.Research Results show that collectively same Service performance and Costumer satisfaction influential Significant agains Loyality depositor Bank Mandiri branch Samarinda.Variable Costumer Satisfaction have influence dominant Loyalty to the obligor Bank Mandiri branch Samarinda. Nugroho ( 2005 : 11 ) declare that to regression compounded better use R Square yes have adjustable or written adjusted R Square method of 0,120 this give a sense 12% of variation variable dependent that is Loyalty of the depositor Bank Mandiri branch Samarinda can descoribed by the independent variable Service Performance and Customer Satisfaction now the rest 88% annotated by factors of variable other unknown and notiucluded in the research.